HUBUNGAN ANTARA KONSEP PERAN GENDER TERHADAP MINAT BELAJAR BIDANG TATA BOGA SISWA LAKI-LAKI KELAS X DI SMK SAHID SURAKARTA - Carissia, Astri (TALENTA, 2013)
The concept of gender roles in adolescent affects in their motivation learning especially in the culinary sector. It is based on the observation in tourism schools. The most students who are continuing their education in the culinary sector are women. The population of the study is 84  male students  of class X  SMK  Sahid  Surakarta. Meanwhile, sample is not used in this study. This  is because  it use  to minimize  errors and generalization of  the results from the research. Pearson product moment analysis that is used  to examine the correlation of variable concepts  from gender roles and culinary learning motivation shows = 0458 with p-value 0.000 <0.01. The conclusion  of  this study  is there  is  a significant correlation  between  concept  of gender roles with learning motivation of the culinary sector from male students of class X at SMK Sahid  Surakarta. The  contribution is  45.80% from the  concept of gender roles in learning motivation of culinary.